2010
DOI: 10.1038/clpt.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of 89Zr-trastuzumab and PET Imaging of HER2-Positive Lesions in Patients With Metastatic Breast Cancer

Abstract: We performed a feasibility study to determine the optimal dosage and time of administration of the monoclonal antibody zirconium-89 ((89)Zr)-trastuzumab to enable positron emission tomography (PET) imaging of human epidermal growth factor receptor 2 (HER2)-positive lesions. Fourteen patients with HER2-positive metastatic breast cancer received 37 MBq of (89)Zr-trastuzumab at one of three doses (10 or 50 mg for those who were trastuzumab-naive and 10 mg for those who were already on trastuzumab treatment). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
630
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(697 citation statements)
references
References 22 publications
25
630
2
6
Order By: Relevance
“…49 Not only has HER2 been exploited as a signaling target via the therapeutic antibody trastuzumab, 50 it has been further utilized as a drug delivery vector in the antibody-drug conjugate trastuzumab emtansine 51 and in clinical imaging of HER2-positive breast cancer. 4043 It should be noted, however, that HER2 is a somewhat unusual internalizing oncology target in that it exhibits extremely high expression levels and that trastuzumab binding does not down-regulate surface HER2, but instead passively recycles after HER2 endocytosis. 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Not only has HER2 been exploited as a signaling target via the therapeutic antibody trastuzumab, 50 it has been further utilized as a drug delivery vector in the antibody-drug conjugate trastuzumab emtansine 51 and in clinical imaging of HER2-positive breast cancer. 4043 It should be noted, however, that HER2 is a somewhat unusual internalizing oncology target in that it exhibits extremely high expression levels and that trastuzumab binding does not down-regulate surface HER2, but instead passively recycles after HER2 endocytosis. 50 …”
Section: Discussionmentioning
confidence: 99%
“…4,23,30 While these early imaging studies were successful, highly expressed non-internalizing targets only represent a fraction of clinically relevant oncology targets since many cell-surface cancer targets are internalizing. For instance, clinical imaging of human epidermal growth factor receptor 2 (HER2)-expressing tumors has been actively pursued via directly labeled antibodies, 40,41 antibody fragments 42 and affibodies 43 in an effort to improve patient selection and response monitoring for HER2-targeted cancer therapies. 44 Fewer examples exist in which internalizing targets have been pretargeted, 20,39 likely due to risk of time-dependent cell surface depletion of TCO moieties available for click reaction through antibody-bound receptor internalization, thereby decreasing image contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Current examples of PET imaging to measure target expression include estrogen receptor imaging and androgen receptor imaging; HER2 imaging; imaging angiogenesis nonspecifically by measuring blood flow and by imaging specific components expressed in neovasculature; and measuring novel targets, such as matrix metalloproteinases. [130][131][132][133][134][135] In all of these cases, PET imaging has the potential to provide prognostic information and can help predict the likelihood that a patient will respond to a targeted chemotherapeutic agent. One of the major imaging agents in this class is 18 F-fluoroestradiol (FES), which has exhibited the most promise in quantifying the functional estrogen receptor status of primary or metastatic breast cancer.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 99%
“…Dijkers et al demonstrated that PET scanning after administration of 89 Zr-trastuzumab at appropriate doses allows visualization and quantification of uptake in HER-2-positive lesions in patients with metastatic breast cancer, even in the brain [16]. A feasibility study in a greater number of patients (Baum et al and Dijkers et al enrolled only 3 and 14 patients, respectively) is needed to clarify the optimal dosage and, for long-lived isotopes, the best time for image acquisition after radiotracer administration.…”
mentioning
confidence: 99%